2014
DOI: 10.1253/circj.cj-13-0238
|View full text |Cite
|
Sign up to set email alerts
|

Incremental Shuttle Walk Test as a Valuable Assessment of Exercise Performance in Patients With Pulmonary Arterial Hypertension

Abstract: Circulation Journal Official Journal of the Japanese Circulation Society http://www. j-circ.or.jp chievement of reliable results in clinical trials requires an accurate assessment technique. Many clinical trials investigating pulmonary arterial hypertension (PAH) have used the 6-min walk test (6MWT) as a clinical endpoint. Measurement of peak oxygen consumption (pV O2) and oxygen consumption at anaerobic threshold (V O2 at AT) via indirect calorimetry provides an objective, reliable and non-invasive technique … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 24 publications
1
17
0
Order By: Relevance
“…However, in a recent meta-analysis of 6MWT findings for PAH patients, improvement in 6MWT results did not reflect benefits in terms of clinical outcomes 12 . The findings of our study confirm those previously reported that CPX is more effective than 6MWT for measuring maximum exercise tolerance for PH patients 13,14 . On the other hand, Lammers et al reported that 6MWT reflects symptomatic maximum exercise test compared with CPX using bicycle ergometry in PH children with a 6MWD below 300m 9 .…”
Section: Assessment Of Exercise Tolerance For Pah and Ctephsupporting
confidence: 92%
“…However, in a recent meta-analysis of 6MWT findings for PAH patients, improvement in 6MWT results did not reflect benefits in terms of clinical outcomes 12 . The findings of our study confirm those previously reported that CPX is more effective than 6MWT for measuring maximum exercise tolerance for PH patients 13,14 . On the other hand, Lammers et al reported that 6MWT reflects symptomatic maximum exercise test compared with CPX using bicycle ergometry in PH children with a 6MWD below 300m 9 .…”
Section: Assessment Of Exercise Tolerance For Pah and Ctephsupporting
confidence: 92%
“…20 A small study in pulmonary hypertension also noted that ISWD correlated more closely with peak oxygen consumption than 6MWT distance. 21 The ISWT has therefore been proposed as an alternative field walking test to the 6MWT in PAH, 22,23 however, there are no long-term data on the prognostic value of the ISWT or its sensitivity to change.…”
Section: Introductionmentioning
confidence: 99%
“…Although the 6MWD is regarded as the gold standard for measuring exercise capacity, we previously reported that SWD showed a greater correlation than 6MWD with both pO 2 and AT. Thus, the shuttle walking test (SWT) is a better reflection of exercise tolerance in PAH than is 6MWD …”
Section: Discussionmentioning
confidence: 99%
“…Thus, the shuttle walking test (SWT) is a better reflection of exercise tolerance in PAH than is 6MWD. 27 Combination therapy is recommended for treatment of PAH. 2 Some clinical trials established supporting evidence for the value of combination therapy.…”
Section: Discussionmentioning
confidence: 99%